Kingdom of the Netherlands-Netherlands : Financial Sector Assessment Program:: Technical Note-Financial Stability and Stress Testing of the Banking, Household, and Corporate Sectors. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for the Netherlands on financial stability and stress testing of the banking, household, and corporate sectors. The Dutch banking system appears resilient to risks. The stress test results indicate that a scenario of extreme adverse macroeconomic conditions would have a significant negative impact on Basel III fully loaded capital ratios, but all banks would maintain capital ratios above minimum regulatory requirements. However, the results for the leverage ratio show that a significant bank could fall just below the fully loaded minimum 3 percent hurdle.